2016
DOI: 10.3329/jdmc.v24i2.29620
|View full text |Cite
|
Sign up to set email alerts
|

Non Compliance Pattern of Anti Hypertensive Treatment

Abstract: Abstract:A cross-sectional type of observational study was conducted on hypertensive patients attending at medicine department (OPD and admitted)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In this study, when the relationship between the education status of the patients and the MMAS-8 score was examined, it was observed that medication adherence increased as the education level increased in hypertensive Studies in diabetic patients in the literature also show that education level does not affect medication adherence, which is consistent with our study (16). Many studies conducted in hypertensive patients have found results that support our research (17).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, when the relationship between the education status of the patients and the MMAS-8 score was examined, it was observed that medication adherence increased as the education level increased in hypertensive Studies in diabetic patients in the literature also show that education level does not affect medication adherence, which is consistent with our study (16). Many studies conducted in hypertensive patients have found results that support our research (17).…”
Section: Discussionsupporting
confidence: 91%